A pedagogia como autogoverno em Johann Friederich Herbart - Neitzel, Odair (2018)
The work investigates the notion of pedagogy in Johann Friedrich Herbart, seeking to understand in what terms the General Pedagogy, his main work, develops the tripartite theory of pedagogical action, known as government, teaching and discipline. Of bibliographical nature, the research adopts the hermeneutic procedure of reading and interpretation of texts, investigating the above mentioned concepts - government, teaching and discipline - and in what sense they justify a new theory of pedagogical action, whose center rests in the formation for self-government. The thesis is divided into four chapters: the first investigates the philosophical and pedagogical heritage of Aufklärung, interpreting the meaning of the concepts of educability and perfectibility, and the way in which these concepts become the starting point of Herbart's pedagogical reflections. The second chapter takes as reference the concept of pedagogical action of the government of the children, signaling to its place like condition of the education in general. The third chapter turns to educational instruction, reflecting on how it is the source of pedagogical action that aims to form the circle of thoughts and multiple interest, which in turn become the basis of the person's ethical character . The fourth and final chapter focuses on the investigation of the formative role of the discipline, trying to show its importance, as a pedagogical action, to strengthen the character of the student and, above all, to develop their ethics. The guiding line of the thesis shows that all the formation process proposed by the General Pedagogy aims to develop the self government ofthe student, avoiding that it is annulled in its capacity to educate and to improve itself.Formation assumes the fundamental presupposition of the subject's exercise of self as the path to the formation of ethics. The research testifies to Herbart's important contribution to philosophy and education and, on the other hand, attests to the limited knowledge that exists in Brazil about the author. The potential of Herbart's thinking is thus evidenced in the face of current controversial problems, such as that of the place of the adult, of the conditions and needs of the child, of the conception of formation and of discipline.